Homozygous whole body Cbs knockout in adult mice features minimal pathology during ageing despite severe homocysteinemia. Issue 4 (22nd March 2022) - Nakladal, D.; Lambooy, S. P. H.; Mišúth, S.; Čepcová, D.; Joschko, C. P.; van Buiten, A.; Goris, M.; Hoogstra‐Berends, F.; Kloosterhuis, N. J.; Huijkman, N.; van de Sluis, B.; Diercks, G. F.; et al.
Abstract: Deficiencies in Cystathionine‐β‐synthase (CBS) lead to hyperhomocysteinemia (HHCy), which is considered a risk factor for cardiovascular, bone and neurological disease. Moreover, CBS is important for the production of cysteine, hydrogen sulfide (H2 S) and glutathione. Studying the biological role of CBS in adult mice has been severely hampered by embryological disturbances and perinatal mortality. To overcome these issues and assess the effects of whole‐body CBS deficiency in adult mice, we engineered and characterized a Cre‐inducible Cbs knockout model during ageing. No perinatal mortality occurred before Cbs −/− induction at 10 weeks of age. Mice were followed until 90 weeks of age and ablation of Cbs was confirmed in liver and kidney but not in brain. Severe HHCy was observed in Cbs −/− (289 ± 58 µM) but not in Cbs +/− or control mice (<10 µM). Cbs −/− showed impaired growth, facial alopecia, endothelial dysfunction in absence of increased mortality, and signs of liver or kidney damage. CBS expression in skin localized to sebaceous glands and epidermis, suggesting local effects of Cbs −/− on alopecia. Cbs −/− showed increased markers of oxidative stress and senescence but expression of other H2 S producing enzymes (CSE and 3‐MST) was not affected. CBS deficiency severely impaired H2 S production capacity in liver, but not in brain or kidney. In summary, Cbs −/− mice presented a mild phenotype without mortality despite severe HHCy. The findings demonstrate that HHCy is not directly linked to development of end organ damage.